Inklusi Sosial Kaum Difabel dalam Perspektif Al-Quran: Analisis Kontesktual Surah ‘Abasa - Mochamad Aris Yusuf (PT. Student Rihlah Indonesia, 2025)
This study aims to examine the social inclusion of people with disabilities from the perspective of the Qur'an with a focus on the contextual analysis of Surah 'Abasa. People with disabilities often experience marginalization and discrimination from society, especially by groups considered